Daya Tarik Aliran Sungai Opak di Wilayah Yogyakarta Sebagai Destinasi Wisata Alam dan Pendidikan. - Wisnu Hadi (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2020)
Abstract – The potential of natural tourism in the Yogyakarta region is widely spread throughout the districts and cities in the Special Region of Yogyakarta Province so that it enriches the treasury of tourism for both local and foreign tourists. The Opak watershed has a positive impact on local residents because there is a lot of potential that can be developed into new tourist destinations so that welfare increases. With a qualitative research method the researcher wants to explain the various tourism objects or tourist destinations in the Opak river basin of Yogyakarta to tourists who want to know the potentials in the area. Retrieval of data using observation of tourism objects and supported by literature related to history and description of tourist destinations in the Opak river area. The Opak watershed has a lot of potential that has already been developed and can be further developed so that it can increase tourist visits. Management of tourist objects while maintaining the rules for continuing to preserve the authenticity of nature along the Opak river basin. The application of Sapta Pesona is the duty of the tour manager so that the quality of service can be carried out optimally. Opak River Yogyakarta will always provide community welfare for residents along the watershed if managed wisely and creativelyKeyword : Attraction, River Flow, Travel DestinationsAbstrak- Potensi wisata alam di wilayah Yogyakarta banyak tersebar di seluruh wilayah kabupaten maupun kota yang ada di Propinsi Daerah Istimewa Yogyakarta sehingga memperkaya khasanah wisata untuk dikunjungi wisatawan daerah maupun asing. Daerah aliran sungai Opak memberi dampak positif kepada warga sekitar karena banyak potensi yang dapat dikembangkan menjadi destinasi wisata baru sehingga kesejahteraan meningkat. Dengan metode penelitian kualitatif peneliti ingin mempaparkan berbagai obyek wisata atau destinasi wisata yang ada di daerah aliran sungai Opak Yogyakarta kepada wisatawan yang ingin mengetahui potensi-potensi yang ada di daerah tersebut. Pengambilan data menggunakan cara observasi  ke obyek wisata serta didukung literature yang berhubungan dengan sejarah serta deskripsi destinasi wisata di daerah sungai Opak tersebut. Kawasan daerah aliran sungai Opak mempunyai banyak potensi yang sudah dikembangkan dan dapat dikembangkan lagi sehingga dapat meningkatkan kunjungan wisata. Pengelolaan obyek wisatanya tetap menjaga kaidah-kaidah untuk terus melestarikan keaslian alam sepanjang daerah aliran sungai Opak. Penerapan Sapta Pesona menjadi kewajiban pengelola wisata agar kualitas pelayanan dapat dilakukan secara optimal. Sungai Opak Yogyakarta akan selalu memberi kesejahteraan masyarakat bagi warga sepanjang daerah aliran sungai jika dikelola secara bijak dan kreatifKata Kunci : Daya Tarik, Aliran Sungai, Destinasi Wisata